Rapid incorporation of a difluoroacetate radical into para-quinone methides via radical 1, 6-conjugate addition. Issue 49 (25th May 2021) - Li, Xin; He, Songtao; Song, Qiuling
Abstract : Presented herein is a newly designed strategy that rapidly introduces ethyl difluoroacetate radicals through a dialkylzincs induced radical 1, 6-conjugate addition pathway. Abstract : Presented herein is a newly designed strategy that rapidly introduces ethyl difluoroacetate radicals through a dialkylzincs induced radical 1, 6-conjugate addition pathway. Besides achieving high yields and excellent functional group compatibility, this protocol allowed the incorporation of a gem -difluoromethylene motif to be accomplished within minutes.